A Binary Logistic Regression Model for Entrepreneurial Intention of Bachelor Business Administration Program in Management Rajamangala University of Technology Suvarnabhumi - Lerdwiwatchaiyaporn , sutathip; Pasunon, Prasopchai (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2025)
This research aims to 1) classify students’ entrepreneurial intentions and 2) predict students’ entrepreneurial intentions. The study collected data using questionnaires from a sample of 276 undergraduate business administration students majoring in management. The data were analyzed using percentages, means, standard deviations, and logistic regression analysis. The findings revealed that in terms of entrepreneurial intention classification, most respondents were male (206 students, 74.6%), while female respondents accounted for 70 students (25.4%). After graduation, 39 students (14.1%) had no intention of becoming entrepreneurs, whereas 237 students (85.9%) intended to pursue entrepreneurship. Regarding individual factors: (1) Innovativeness was rated at a high level of satisfaction, with a mean score of 4.40 ( = 4.40, SD = 0.53). (2) Risk-Taking was rated the highest, with a mean score of 4.52 ( = 4.52, SD = 0.51). (3) Internal Locus of Control was rated at a high level of satisfaction, with a mean score of 3.92 ( = 3.92, SD = 0.56). (4) Need for Achievement was rated at a high level of satisfaction, with a mean score of 3.98 ( = 3.98, SD = 0.47). (5) Family Background was rated at a high level of satisfaction, with a mean score of 3.99 ( = 3.99, SD = 0.42). The prediction analysis indicated that three variables significantly influenced entrepreneurial intention: innovativeness (Sig. = .000), risk-taking (Sig. = .034), and need for achievement (Sig. = .021), all of which had a positive effect at a significance level of 0.05. These findings suggest that students who intend to become entrepreneurs should develop these skills to increase their chances of success in entrepreneurship.